Cold Plasma Treatment Alters the Morphology, Oxidative Stress Response and Specialized Metabolite Content in Yellow Iris (I. reichenbachii) Callus - Slađana Jevremović; Milica Milutinović; Ksenija Veličković; Uroš Gašić; Nikola Škoro; Nevena Puač; Suzana Živković (Horticulturae, 2025)
The application of non-thermal (cold) plasmas is considered an environmentally friendly method that could affect plant metabolism and cellular development or can be used for the commercial production of natural products that cannot be chemically synthesized. In the present study, the non-embryogenic callus of iris (Iris reichenbachii Heuff.) was treated with a Radio Frequency (RF) plasma needle device using He as a working gas. We investigated short-term (up to seven days) and long-term (up to one year) changes on morphological, physiological and biochemical levels. An increased production of O2− and H2O2 was observed in the callus tissue after plasma treatment. The enzymes SOD and CAT represented the frontline in the antioxidant defense against reactive oxygen species (ROS) produced during the first hour of treatment, while POX was the leading antioxidant enzyme seven days after plasma treatment. Significant long-term morphological changes were observed in the calli due to the increased mitotic activity of the plant cells. In addition, three flavonoids (naringenin, apigenin and acacetin) and two isoflavonoids (irisolidone and irilone) were detected only in the plasma-treated tissue even one year after plasma treatment. The present study emphasizes the application of the plasma technique to promote meristematic activity and stimulate the production of specialized metabolites in iris calli.